1988
DOI: 10.1080/0028825x.1988.10410642
|View full text |Cite
|
Sign up to set email alerts
|

Mountain beech (Nothofagus solandrivar.cliffortioides) decline in the Kaweka Range, North Island, New Zealand

Abstract: Forest dieback in the Kaweka Range appears to be a stage in the natural process of replacement for mountain beech. An examination of stand structure in stable, transitional, and unstable forest showed dieback and tree mortality to be associated with mature and over mature stands. Recruitment peaks suggest periodic natural disturbance, such as severe drought, initiates tree decline. Insects and disease, although contributing to the rate of decline, were shown to be symptoms rather than causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…5; Table A3), multi-year droughts have repeatedly triggered widespread Eucalyptus and Corymbia mortality (Fensham and Holman, 1999;Rice et al, 2004;Fensham and Fairfax, 2007), and have also caused tree death in Acacia woodlands (Fensham and Fairfax, 2005). There is also documentation of drought-induced mortality in temperate Nothofagus forests in New Zealand (Hosking and Hutcheson, 1988).…”
Section: Examples Of Recent Climate-induced Forest Mortalitymentioning
confidence: 97%
“…5; Table A3), multi-year droughts have repeatedly triggered widespread Eucalyptus and Corymbia mortality (Fensham and Holman, 1999;Rice et al, 2004;Fensham and Fairfax, 2007), and have also caused tree death in Acacia woodlands (Fensham and Fairfax, 2005). There is also documentation of drought-induced mortality in temperate Nothofagus forests in New Zealand (Hosking and Hutcheson, 1988).…”
Section: Examples Of Recent Climate-induced Forest Mortalitymentioning
confidence: 97%
“…NM, Buller (69287). Hosking & Hutcheson (1988) reported that Nodulisporium sp. was consistently isolated from wilting twigs of Nothofagus solandri var.…”
Section: Junghuhniamentioning
confidence: 99%
“…In the absence of exogenous stand-destroying disturbance, synchronous stand dieback is an important component of forest change in pure stands of Fuscospora spp., initiated by snow break, wind damage, drought, and insect attack, for example (Wardle & Allen 1983;Hosking & Hutcheson 1988;Ogden 1988;Ogden et al 1996). Either one or a combination of these stressors can initiate dieback, and initial mortality from one stressor may lead to further mortality from another (Ogden et al 1996).…”
Section: Descriptions Of Forest Change For New Zealand Beech Forestsmentioning
confidence: 99%